Legal Aspects of Humanitarian Intervention (Annual of the Faculty of Philosophy in Skopje, 2017)
There is a question raised of whether the forced humanitarian intervention is to be justified in contrast to clear contradiction in the classical law of interstate relations. The classic approach puts emphasis on the principle of sovereignty, even in case when the state becomes enforcer of human rights abuses against its own citizens, or when the state decays with a civil war, crisis or civil unrest. In this paper the author explores the security debate over the implementation of il/legal intervention driven by the imperative of responsibility to protect. The author argues that humanitarian intervention despite ambiguities and controversies about its application, has slowly led to the concept of responsibility to protect vulnerable populations. This approach is based on the priority of human security in relation to the national security and the importance of protection of civilians as persistent disagreement between state sovereignty and intervention. After the end of the Cold War, the international community has found assets and willingness to do something about the colapsed and the failed states. Until that time, if humanitarian interventions were rare and were considered illegal, suddenly the United Nations started organizing and sponsoring a number of peacekeeping operations. It is a matter of transition from traditional peacekeeping to more ambitious peacemaking operations. Hence, the issue of balance between the existing consent for peacekeeping operations on one hand and the readiness to use force against those who break the peace agreements and oppose humanitarian missions on the other hand, was raised. There are divided views of the protagonists and the opponents of intervention and humanitarian missions. The views are divided by the political dilemma of desire for something to be done, despite the risk of mission failure. Analysis of the politics behind humanitarian interventions must take into account the public opinion and the politics of the Security Council of the UN. Legality asside, a significant problem still remains in the implementation of humanitarian operations, particularly in terms of funding the UN, despite the general view that there is optimism in the international community for humanitarian peacekeeping activities.
Keywords: HUMANITARIAN INTERVENTION; DICHOTOMY; PROTECTION OF CIVILIANS; HUMANITARIAN LAW; UN